IMPROVING STUDENT’S VOCABULARY THROUGH GUESSING GAMES TECHNIQUE IN DESCRIPTIVE TEXT IN SPEAKING - Niarti, Agus; ., Ikhsanudin; ., Wardah (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2016)
Abstract : This research aimed at finding out whether the students? vocabulary can be improved after the teaching and learning process using guessing games technique in descriptive text. The writer conducts an action research entitled ?Improving Student?s Vocabulary Through Guessing Games Technique in Descriptive Text in Speaking?. The sample of this research is the third grade students of SD Islam Terpadu Haruniyah Pontianak Timur in academic year 2015/2016. The technique employed in this research is guessing games. The procedure of the research consists of identifying the problem, planning action, implementing, observing, reflecting the result of the observing and revising the plan. The result of this research showed that guessing games improve student?s vocabulary in descriptive text. In conclusion, the use of guessing games technique in teaching English can improve the vocabulary of the third grade students of SD Islam Terpadu Haruniyah Pontianak Timur. Key Words :  Vocabulary, Guessing Games, Descriptive Text   Abstrak: Penelitian ini bertujuan untuk mengetahui apakah kosakata siswa dapat ditingkatkan melalui proses pengajaran dan pembelajaran menggunakan teknik permainan menebak dalam teks deskriptif. Penulis melakukan tindakan berjudul ?Meningkatkan Kosakata Siswa Melalui Teknik Permainan Tebakan dalam Teks Deskriptif dalam Berbicara?. Sampel dari penelitian ini adalah siswa kelas tiga SD Islam Terpadu Haruniyah Pontianak Timur tahun ajaran 2015/ 2016. Teknik yang digunakan dalam penelitian ini adalah permainan tebakan. Prosedur penelitian  terdiri dari mengidentifikasi masalah, perencanaan tindakan, pelaksanaan, mengamati, menggambarkan hasil dari pengamatan dan memperbaiki perencanaan. Hasil dari penelitian menunjukan bahwa permainan tebakan meningkatkan kosakata siswa dalam teks deskriptif. Kesimpulannya, menggunakan teknik permainan tebakan dalam mengajar bahasa inggris dapat meningkatkan kosakata pada siswa kelas tiga SD Islam Terpadu Haruniyah Pontianak Timur. Kata Kunci : Kosa Kata, Permainan Tebakan, Teks Deskriptif